Organophosphates and monocyte esterase deficiency. Issue 8 (August 1995) - McClean, E; Mackey, H; Markey, G M; Morris, T C
Abstract : AIMS–To examine the possibility that monocyte esterase deficiency (MED) could be caused by exposure to organophosphates. METHODS–Pseudocholinesterase, paraoxonase and arylesterase activities were measured in the serum and acetylcholinesterase activity was measured in the red cells of a group of monocyte esterase deficient subjects and compared with the enzyme activities of a control group of monocyte esterase positive subjects. RESULTS–No significant difference was found between the enzyme activities of the monocyte esterase deficient group and the control group for any of the esterases investigated. CONCLUSION–Current or recent exposure to organophosphorus is not the cause of MED.